2015
DOI: 10.1513/annalsats.201411-506oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Positive Airway Pressure on Patients with Obstructive Sleep Apnea during Acute Ascent to Altitude

Abstract: Rationale: In acute ascent to altitude, untreated obstructive sleep apnea (OSA) is often replaced with central sleep apnea (CSA). In patients with obstructive sleep apnea who travel to altitude, it is unknown whether their home positive airway pressure (PAP) settings are sufficient to treat their obstructive sleep apnea, or altitude-associated central sleep apnea.Methods: Ten participants with positive airway pressure-treated obstructive sleep apnea, who reside at 1,320 m altitude, underwent polysomnography on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The changes are more marked in those with severe OSAS. Use of CPAP at altitude is associated with decreased central sleep apnoea and increased sleep efficiency 116…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes are more marked in those with severe OSAS. Use of CPAP at altitude is associated with decreased central sleep apnoea and increased sleep efficiency 116…”
Section: Methodsmentioning
confidence: 99%
“…Using hypobaric chamber simulation testing, studies have shown that there is an association between hypoxaemia, decreased sleep time and an increased frequency of hypopneas for patients with OSAS who are acutely exposed to high altitude. 116 There are further adverse effects on sleep and OSAS if alcohol 117 or sedatives 118 are taken.…”
Section: Osas and Ohsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a bioinformatics-based study whereby de-identified data obtained from the national-level adherence database (EncoreAnywhere ® ™, Philips-Respironics, Inc., Murrysville, PA, USA) was geo-linked to publicly available de-identified data that provides median household income information by 5-digit ZIP code of residence contained in both datasets [22,23]. Similarly, information regarding altitude was obtained and geo-linked because there is data suggesting that central apneas are worsened by high altitude and in a population-level analysis such apneas could influence adherence adversely [18,24]. Institutional Review Board approval was obtained from the University of Arizona (Protocol #1609849884).…”
Section: Methodsmentioning
confidence: 99%